circRNA Hipk3 Induces Cardiac Regeneration after Myocardial Infarction in Mice by Binding to Notch1 and miR-133a - Xiaoyun Si; Hao Zheng; Guoquan Wei; Mengsha Li; Wei Li; Houmei Wang; Haijun Guo; Jie Sun; Chuling Li; Shenrong Zhong; Wangjun Liao; Yulin Liao; et al. (Elsevier, 2020)
The synergism between cardiomyogenesis and angiogenesis is essential for cardiac regeneration. Circular RNAs (circRNAs) play pivotal roles in cell growth and angiogenesis, but their functions in cardiac regeneration are not yet known. In this study, we investigated the role and underlying mechanisms of circRNA Hipk3 (circHipk3) in both cardiomyogenesis and angiogenesis during cardiac regeneration. We found that circHipk3 was overexpressed in the fetal or neonatal heart of mice. The transcription factor Gata4 bound to the circHipk3 promoter and increased circHipk3 expression. Cardiomyocyte (CM) proliferation in vitro and in vivo was inhibited by circHipk3 knockdown and increased by circHipk3 overexpression. Moreover, circHipk3 overexpression promoted coronary vessel endothelial cell proliferation, migration, and tube-forming capacity and subsequent angiogenesis. More importantly, circHipk3 overexpression attenuated cardiac dysfunction and decreased fibrotic area after myocardial infarction (MI). Mechanistically, circHipk3 promoted CM proliferation by increasing Notch1 intracellular domain (N1ICD) acetylation, thereby increasing N1ICD stability and preventing its degradation. In addition, circHipk3 acted as a sponge for microRNA (miR)-133a to promote connective tissue growth factor (CTGF) expression, which activated endothelial cells. Our findings suggested that circHipk3 might be a novel therapeutic target for preventing heart failure post-MI.